Omnibus Law on Job Creation: State Capture? - Ambarwati, Siska (Jurnal Media Hukum, 2021)
The study aims to analyze whether there is a state capture in making the Job Creation Law. Since the Job Creation Law was raised, many parties have criticized the existence of the Law because in the making of the Job Creation Law it is believed that it is more beneficial to employers, giving rise to an indication of state capture in its making. The research method used is a form of normative research with a statutory approach. The result shows that there is a state capture carried out by the authorities and employers in the making of the Job Creation Law. About 262 or 45.5 percent of the 575 House of Representatives members are affiliated with the company and therefore the regulations to be made more favorable for employers or investors while the welfare of workers is at stake. The rushed legislative process causes the values and aspirations of the people to be unable to be proportionally aggregated and accommodated, and this is certainly contrary to the principle of participation and the principle of openness as stipulated in the provisions of laws and regulations.